2011
DOI: 10.1086/660100
|View full text |Cite
|
Sign up to set email alerts
|

Hand Hygiene, and Not Ertapenem Use, Contributed to Reduction of Carbapenem-Resistant Pseudomonas aeruginosa Rates

Abstract: Use of alcohol-based hand gel, rather than ertapenem, was associated with a reduction in the rates of carbapenem-resistant P. aeruginosa infection. Measures to reduce resistance must include factors other than just antimicrobial stewardship programs alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…However, ASPs have been shown to be cost-effective and to reduce costs in the long term [ 46 ]. ASPs should be implemented alongside other effective interventions such as hand hygiene, which has been shown to reduce antimicrobial resistant infections [ 52 ]. Furthermore, across all income settings it will be important to promote integration with other programmes for pharmacy management, microbiology, POC diagnostics and laboratory quality control [ 46 ].…”
Section: Prevention and Treatmentmentioning
confidence: 99%
“…However, ASPs have been shown to be cost-effective and to reduce costs in the long term [ 46 ]. ASPs should be implemented alongside other effective interventions such as hand hygiene, which has been shown to reduce antimicrobial resistant infections [ 52 ]. Furthermore, across all income settings it will be important to promote integration with other programmes for pharmacy management, microbiology, POC diagnostics and laboratory quality control [ 46 ].…”
Section: Prevention and Treatmentmentioning
confidence: 99%
“…In contrast, the marked rise in the use of alcohol hand rub may have impacted the emergence of resistance by decreasing the nosocomial transmission of MDR organisms; although this relationship was not observed in the multivariable analysis in the present study, as was found by a recent study in a Brazilian hospital. 24 The non-significant association could be due to the modest use of the alcohol-based antiseptic solution at our institution, where bedside dispensers were not systematically installed until 2010. Although no systematic epidemiological research has been conducted, it is plausible that, in contrast with mostly polyclonal imipenem-resistant P. aeruginosa, primarily related to OprD loss, carbapenemases are much more common in Acinetobacter spp., which makes infection control practices more important than antibiotic interventions for carbapenem resistance.…”
Section: Discussionmentioning
confidence: 95%
“…Increasing education around hand hygiene practices must be coupled with supplying the means to perform hygiene easily, and seems to be a reasonable first step forward in LMICs to control the spread of resistant organisms and reduce HCAIs. Importantly, increased hand hygiene has been shown to correlate with a reduction in antimicrobial resistance[90] and HCAIs[91]. …”
Section: Turning the Tide Of Antimicrobial Resistance: Interventions mentioning
confidence: 99%